From Genesis to genetics : the case of evolution and creationism - Moore, John Alexander, 1915-2002 (University of California Press, 2002)
The clash between evolution and creationism is one of the most hotly contested topics in education today. This book, written by one of America's most distinguished science educators, provides essential background information on this difficult and important controversy.